S-Linear Almost Distributive Lattices (European Journal of Pure and Applied Mathematics, 2010)
The concept of an S − Linear ADL is defined and characterized interms of the S − prime ideals and S − prime filters.  Equivalent condition for an ADL R to become a (dually)B − relatively normal ADL in terms of minimal prime ideals(filters) and B − maximal ideals(filters) is obtained, where B is the Birkhoff centre of R.